Effects of the interplanetary magnetic field on the characteristics of Pc 3-4 pulsations at globally coordinated stations - Yumoto,Kiyohumi; Saito,Takao; Tsurutani,Bruce T.; Smith,Edward J.; Akasofu,Syun-Ichi (1985)
P(論文) Daytime Pc 3-4 pulsation activities observed at globally coordinated low-latitude stations [SGC (L=1.8,λ=118.0°W), EWA (1.15,158.1°W), ONW (1.3,141.5°E)] are evidently controlled by the cone angle θ_<XB> of the IMF observed at ISEE 3. Moreover, the Pc 3-4 frequencies (ƒ) at the low latitudes and high latitude (COL; L=5.6 and λ=147.9°W) on the ground and that of compressional waves at geosynchronous orbit (GOES 2; L=6.67 and λ=106.7°W) are simultaneously correlated with the IMF magnitude (B_ ). The correlation of ƒ of the compressional Pc 3-4 waves at GOES 2 against B_ is higher than those of the Pc 3-4 pulsations at the globally coordinated ground stations, i. e., γ=0.70 at GOES 2,and (0.36,0.60,0.66,0.54) at (COL, SGC, EWA, ONW), respectively. The standard deviation (σ_n=±ΔƒmHz) of the observed frequencies from the form ƒ (mHz)=6.0×B_ (nT) is larger at the ground stations than at GOES 2,i. e., Δƒ=±6.6mHz at GOES 2,and ±(13.9,9.1,10.7,12.1) mHz at (COL, SGC, EWA, ONW), respectively. The correlations between the IMF magnitude B_ and Pc 3-4 frequencies at the low latitudes are higher than that at the high latitude on the ground, which can be interpreted as a "filtering action" of the magnetosphere for daytime Pc 3-4 magnetic pulsations. The scatter plots of pulsation frequencies observed in the magnetosphere versus the IMF magnitude show a remarkable distribution restricted within the forms of ƒ=4.5×B_ and ƒ=7.5×B_ . The observed frequency range is theoretically confirmed to be consistent with the inferred frequency range (ω_/Ω_i=0.3-0.5) in the spacecraft frame of the magnetosonic upstream waves excited by the anomalous ion cyclotron resonance with reflected ion beams, which is observed to be V_∥=650-1150km/s in the solar wind frame by the ISEE satellite in the earth's foreshock. It is concluded that the magnetosonic right-handed waves excited by the reflected ion beams in the earth's foreshock are convected through the magnetosheath to the magnetopause, being transmitted into the ...